José Ramón Mélida, un arqueólogo entre dos estilos - Casado Rigalt, Daniel (Gerión. Revista de Historia Antigua, 2006)
José Ramón Mélida, an archaeologist between two styles. José Ramón Mélida is the most important archaeologist in the period between 1875 and 1936. Being a heir of the former antiquarian tradition, he knew how to conform the old Archaeology to the Positive and Scientific Principles. Thanks to his contact with French hispanists he could approach the Spanish and the European Archaeologies together. He tried the Spanish Archaeology to get closer to the European one, as well as to be got rid of its political bias. He took part in the excavations of Numantia and Augusta Emerita. He also gained a position as manager of Museo de Reproducciones Artísticas and Museo Arqueológico Nacional.